Kerusakan Lingkungan Akibat Sampah Kulit Kerang di Situs Kota Cina Medan - Repelita Wahyu Oetomo (PURBAWIDYA: Jurnal Penelitian dan Pengembangan Arkeologi, 2022)
The China Town in the past was one of the important trading ports in the archipelago, this is proven by the abundance of findings from archaeological excavations at the site. The decline of China Town as a trading city is recorded in people's memories in the form of speech stories. The story that is quite well known and developed in the community that makes China Town abandoned by its inhabitants is due to the attack of kepah (a type of sea shell) that comes from the sea. As a result, people flocked to leave the city. This story continues to this day. This paper aims to explain scientifically the speech stories that developed in the community associated with data from archaeological research that has been carried out at the site. From the results of excavations carried out, it is found that in various locations, kitchen waste is almost always found in the form of concentrations of shells. This results in environmental damage in the form of river silting, and the closure of the soil surface due to shell waste. These two things make China Town uncomfortable to live in and then abandoned.